IL-2 and IL-15 augment HBV therapeutic vaccination and PD1 blockade for functional cure in the AAV-HBV mouse model - Lewis, Gavin; Malo, Kirsten; Rowland, Thomas; Hooks, Jenaya; Liu, Hao Yuan; Popli, Sonam; Kukolj, George; Pace, Craig S. (Frontiers in Immunology, 2025)
IntroductionPrevalence of chronic hepatitis B virus (HBV) infection remains a major global health issue. Research into a cure has focused on finite combinatorial interventions that aim to reduce HBV surface antigen (HBsAg), suppress virus specific immune tolerance, and induce an adaptive response that functionally controls the virus.MethodsIn C57BL/6 mice transduced with adeno-associated virus encoding the HBV genome, which replicate HBV and persistently express HBsAg at 104 IU/mL or higher, a combination of small interfering RNA (siRNA) knockdown of HBsAg expression followed by immunization with a self amplifying RNA therapeutic HBV vaccine failed to establish HBV control. Using this in vivo murine model, we screened for immunomodulatory agents added after HBV siRNA knockdown, and in combination with therapeutic vaccination, that may enhance the HBV adaptive immune response to control HBV. Results/DiscussionIn mice with very high levels of HBsAg (104–105 IU/mL), levels that are observed clinically during standard HBV therapy and that were brought low (102 IU/mL) by HBV siRNA pre-treatment prior to therapeutic vaccination, PDL1 blockade in combination with stabilized cytokines IL-2 or IL-15 led to immune control of HBsAg in vaccinated animals.